DISIPLIN K3 MELALUI PEMAKAIAN ALAT PELINDUNG DIRI (APD) DI LABORATORIUM KIMIA PT SUCOFINDO - Tatan Sukwika; Susan Endah Kartikasari (Dian Nuswantoro Semarang, 2021)
Chemical laboratories are environments where a wide variety of analytical activities are associated with hazardous chemicals that can have negative implications for occupational safety and health (OSH). The research objective is to analyze the level of discipline based on knowledge, attitudes and commitment to carry out OSH by PT Sucofindo employees in the chemical laboratory. The method used is crosstab analysis and multiple regression analysis. The results of the crosstab analysis showed that there was an influence between age and sex, but there was no effect of working time on the use of PPE. The multiple regression results show that there is a simultaneous influence on the four variables mentioned above with OSH behavior. As for partially, there is an influence between knowledge, PPE facilities and supervision on OSH behaviour there is no influence on supervision. It is recommended that a refresher and outreach should be done regarding the use of PPE, providing PPE equipment needed and supervising the use of PPE at least once time a month in a chemical laboratory.